The grandest game eaudiobook - Barnes, Jennifer Lynn (The Grandest Game, 2024)
Get ready for a new series that brings readers deeper into the lush, romantic, and puzzle-filled world of the #1 bestselling Inheritance Games series (over 3 million copies sold!), set a year after we last saw Avery and the Hawthornes. Seven tickets. An island of dreams. The chance of a lifetime. Welcome to the Grandest Game, an annual competition run by billionaire Avery Grambs and the four infamous Hawthorne brothers, whose family fortune she inherited. Designed to give anyone a shot at fame and fortune, this year's game requires one of seven golden tickets to enter. With millions on the line, those seven players will do whatever it takes to win. Some of the players are in it for the money. Some for power. Some for reasons all their own. Every single one of them has secrets. Amidst it all is Grayson Hawthorne, tasked with a vital role in this year's game. But as tensions rise and the mind-bending challenges push the players to their limits—physically, mentally, and emotionally—it soon becomes clear that not everyone is playing by the rules. #1 New York Times bestselling author Jennifer Lynn Barnes delivers a brand-new series in the world of The Inheritance Games, where fan-favorite and new characters collide in a game you'll never forget. Do you have what it takes to play? Audiobook Edition is read by Anjali Kunapaneni (as GiGi), Christine Lakin (as Lyra), and Zachary Webber (as Rohan).